Exploring Curing Distances and Their Influence on Orthodontic Bracket Bond Strength: In Vitro Research - Anila Rupa Kujur; Simran Suhani; Chandra Lekha (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Chronic urticaria (CU) is defined by the presence of recurrent wheals, angioedema, or both for more than six weeks. In the absence of identifiable triggers, it is termed as chronic spontaneous urticarial (CSU). Several systemic conditions, including thyroid dysfunctions, are implicated in CSU, making early diagnosis crucial for effective management. Case Presentation: The authors present the case of a 30-year-old female dentist who reported with recurrent facial urticaria refractory to antihistamines. Medical history revealed previously diagnosed hypothyroidism for which she had discontinued levothyroxine on her own. Laboratory investigations revealed elevated TSH and low free T3/ T4 levels, confirming primary hypothyroidism. Other causes: autoimmune thyroiditis, infection, anemia, systemic conditions were ruled out, and the patient was referred to an endocrinologist. On restarting levothyroxine, complete, sustained remission was achieved. Conclusion: Facial urticaria, though unusual, may be the only presenting feature of CSU. It should prompt clinicians, especially dental practitioners, to consider systemic associations. Early recognition, a multidisciplinary approach, and targeted therapy for the underlying condition help in achieving remission.